A floristic inventory of the epizoic algae and their associates from inland waters of Bangladesh. Issue 1 (2nd January 2016) - Azam, Shah Md Golam Gousul; Naz, Sabrina; Zafar, Mst Sharmin
Abstract : The diversity of epizoic algae and their associates occurring on the body surface of aquatic animals in 35 permanent and 15 temporary lentic water bodies of Rajshahi University, Bangladesh and its adjacent area has been studied. In all 35 genera and 82 species have been recorded of which 16 genera and 51 species belonged to Chlorophyceae, 11 genera and 21 species to Cyanophyceae, seven genera and nine species to Bacillariophyceae and one genus and species to Euglenophyceae. The environmental parameters at which the epizoic algae occurred were a pH of 7.4–8.2 and a water temperature of 19.4–32.1°C.